3D Printed Skin‐Inspired Flexible Pressure Sensor with Gradient Porous Structure for Tunable High Sensitivity and Wide Linearity Range. Issue 7 (9th December 2021) - Zhu, Guotao; Dai, Hongtao; Yao, Yao; Tang, Wenlai; Shi, Jianping; Yang, Jiquan; Zhu, Liya
Abstract: Advanced nanomaterials and novel microstructures have been developed to achieve flexible piezoresistive pressure sensors with high sensitivity and wide linearity range. However, the theoretical relationships between the sensitivity and the structure of the flexible pressure sensor have rarely been established. Consequently, the sensitivities of the sensors cannot be controlled and tailored for practical application. In this work, a skin‐inspired flexible pressure sensor with gradient porous structure is proposed. Based on the stress distribution of finite element analysis (FEA), the quantitative descriptions between the sensitivity and sensor structure parameters are derived. Then, carbon black (CB)/polydimethylsiloxane (PDMS) composites are successfully fabricated with desired gradient porous structures by 3D printing technology. Encouragingly, the skin‐inspired gradient structure sensor shows good sensitivity (0.0048 kPa −1 ) over the ultrawide linear range of 0–500 kPa. Meanwhile, the sensor shows excellent stability and durability during over 500 compression cycles. Taking advantage of these excellent sensing properties, the skin‐inspired gradient porous sensor is demonstrated in the application of voice recognition, grasp sensing, and intermittent pneumatic compression (IPC) interface pressure monitoring. Abstract : A skin‐inspired flexible pressure sensor with gradient porous structure is achieved by direct ink printing method. It shows good sensitivity (0.0048 kPa −1 ) over the ultrawide linear range of 0–500 kPa. The sensitivity can be well tuned by varying the pore characteristics and distribution. The sensor can detect human motions and physical activities from voice recognition to IPC interface pressure detection.